Women Empowerment for Cancer Prevention and Control – lessons from Kerala State - Jayakrishnan, R; Sebastian, Paul; Chennath, Kalavathy Mathur; Thomas, Soya (Indian Journal of Community Health, 2018)
Background: Common cancers occurring in India are either preventable or curable, if detected early. Women’s organisation in Kerala working for poverty eradication was utilized to disseminate the message of cancer prevention in a southern district of Kerala state. Objectives: To create awareness among the community on cancer prevention and motivate them for early detection utilizing trained volunteers. Material and methods: Based on the three-tier system of functioning, master trainers at the top level of the organization were trained initially on primary prevention and early detection of common cancers viz. oral and breast. The trained resource persons further conducted awareness programmes in the second level and later at the grass root level also called the Neighborhood groups. Results: 174 master trainers were trained initially and further utilized to sensitize 920 members at the second level. At the NHG level, 1,00,257 volunteers were sensitized. 39169 house visits were conducted by trained volunteers to create cancer awareness in the community. Conclusion: Cancer literacy mission could effectively be implemented by empowered women in the community. Their acceptance in the community reinforces the fact that they can act both as a messenger for cancer prevention and a source of motivation for early detection.